The Determinants of Purchasing Decisions: The Case of Snack Products - Paramita, Eristia Lidia; Sanjaya, Wahyuni Ratna (Jurnal Organisasi dan Manajemen, 2020)
Parents’ decisions to buy snacks are likely influenced by packaging designs, the colors of the snack packagings, and their children. Children are unique influencers because they cannot afford to buy snacks they desire, but they can influence and even direct their parents to buy the desired snacks. In this article, I investigate how snack packaging designs and colors attract consumers’ attention and affect their purchasing decisions. In particular, this study seeks to analyze the effects of snack packaging design and snack packaging color on parents’ purchasing decisions. The data was generated by using questionnaires that asked 90 parents who have children aged 4-7 years old. Findings. The Study demonstrate that snack packaging designs and colors affect parents’ purchasing decisions.